2011
DOI: 10.1021/ic201008v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Chemical Stability, and Electrical Properties of Nb-, Zr-, and Nb-Codoped BaCeO3 Perovskites

Abstract: We report the effect of donor-doped perovskite-type BaCeO(3) on the chemical stability in CO(2) and boiling H(2)O and electrical transport properties in various gas atmospheres that include ambient air, N(2), H(2), and wet and dry H(2). Formation of perovskite-like BaCe(1-x)Nb(x)O(3±δ) and BaCe(0.9-x)Zr(x)Nb(0.1)O(3±δ) (x = 0.1; 0.2) was confirmed using powder X-ray diffraction (XRD) and electron diffraction (ED). The lattice constant was found to decrease with increasing Nb in BaCe(1-x)Nb(x)O(3±δ), which is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…27,[39][40][41] Very recently, we demonstrated that Gd+Pr co-doped BCs (BCGP) could achieve electrical conductivities comparable to those of Y-doped BCs, but their stability remained poor under CO 2 , as with the majority of doped BCs. 42,43 Moreover, Gd+Pr have higher electronegativity and ionic radius characteristics than those of Y+Yb (electronegativity of Gd : Pr is 1.2 : 1.13 against the 1.22 : 1.1 of Y : Yb, and ionic radius in the octahedral coordination 93.8 : 99 pm versus 90 : 86 pm respectively). Since Zr is known to increase the stability as in the case of Y doping where only after doping with Zr they achieved significant stability, it is imperative that we continue our pursuit of a chemically stable solid electrolyte for SOFCs without surrendering much proton conductivity by systematically introducing Zr in BCGP.…”
Section: Introductionmentioning
confidence: 98%
“…27,[39][40][41] Very recently, we demonstrated that Gd+Pr co-doped BCs (BCGP) could achieve electrical conductivities comparable to those of Y-doped BCs, but their stability remained poor under CO 2 , as with the majority of doped BCs. 42,43 Moreover, Gd+Pr have higher electronegativity and ionic radius characteristics than those of Y+Yb (electronegativity of Gd : Pr is 1.2 : 1.13 against the 1.22 : 1.1 of Y : Yb, and ionic radius in the octahedral coordination 93.8 : 99 pm versus 90 : 86 pm respectively). Since Zr is known to increase the stability as in the case of Y doping where only after doping with Zr they achieved significant stability, it is imperative that we continue our pursuit of a chemically stable solid electrolyte for SOFCs without surrendering much proton conductivity by systematically introducing Zr in BCGP.…”
Section: Introductionmentioning
confidence: 98%
“…BaCeO 3 and BaZrO 3 have been extensively studied as electrolytes for proton-conducting solid oxide fuel cells (H-SOFCs) owing to their high H + conductivity [3]. However, BaCeO 3 decompose under water vapor and CO 2 conditions (Equation 1 and 2) [4][5][6][7][8][9]. BaCeO 3 is thermodynamically unstable under CO 2 atmosphere below ~ 1040 o C and under water vapour (P H2O = 0:5 atm) below ~ 404 o C (equation 1) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Acceptor doping of the perovskite creates oxide ion vacancies (V •• o ) in the perovskite structure. Incorporation of H 2 O into these (V •• o ) sites will create mobile proton charge carriers (H + ) (Iwahara et al, 1981). These physical properties make them attractive membranes for proton conducting solid oxide fuel cells (H-SOFCs), H 2 pumps, gas separation, and steam electrolyzers (Schober, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the lower ionic conductivity, acceptor dopants have been introduced to the B-site in order to increase the V •• o and subsequent proton concentration upon H 2 O incorporation into the oxide ion vacancies through reaction (1) (Iwahara et al, 1981;Knight, 1999;Kreuer, 1999;Shimura et al, 2005;Azimova and McIntosh, 2009;Ricote and Bonanos, 2010;Zhao et al, 2010),…”
Section: Introductionmentioning
confidence: 99%